Physicochemical Properties of Rice Fortified with Payangka Fish Protein Hydrolysate - Iskandar, Ashar; Fatimah, Feti; Aloanis, Anderson (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2025)
Rice is an energy source that is high in carbohydrates and contributes to providing the largest percentage of calories, but rice has a low protein, vitamin and mineral content, so it needs to be fortified to increase the nutritional content of rice, especially protein. This research aims to characterize rice that has been fortified with protein hydrolyzate. Synthesis of Payangka fish protein hydrolyzate was carried out using papain enzyme with concentrations of 2,4 and 6% with an incubation time of 2 hours. The best fortification of rice is done by soaking the rice for 4 hours, then drying it again for 14 hours at a temperature of 50oC. The research results show that Payangka fish hydrolyzate can be obtained through hydrolysis of Payangka fish meat using the Papain enzyme with a concentration of 2-6%. The highest protein content of protein hydrolyzate was obtained when using a Papain enzyme concentration of 6% with a protein content of 3.61%. Fortification of rice with Payangka fish protein hydrolyzate can increase rice protein content, namely from 9.43% (before fortification) to 10.38% (after fortification using protein hydrolyzate with a concentration of 30%)